Organic Matter Composition of Digestates Has a Stronger Influence on N2O Emissions than the Supply of Ammoniacal Nitrogen - Petrova, Ioana Petrova; Pekrun, Carola; Möller, Kurt (Agronomy (Basel), 2021)
Manures can be treated by solid–liquid separation and more sophisticated, subsequent approaches. These processes generate fertilizers, which may differ in composition and N2O release potential. The aim of the study was to investigate the influence of processing-related changes in digestate composition on soil-derived N2O emissions after application to soil. For that purpose, N2O emissions within the first 7 weeks after fertilization with two raw and eight processed digestates (derived from solid–liquid separation, drying and pelletizing of separated solid, and vacuum evaporation of separated liquid) were measured in the field in 2015 and 2016. Additionally, an incubation experiment was run for 51 days to further investigate the effect of subsequent solid and liquid processing on soil-derived N2O release. The results showed that, only in 2016, the separation of digestate into solid and liquid fractions led to a decrease in N2O emissions in the following order: raw digestate > separated liquid > separated solid. N removal during subsequent processing of separated solid and liquid did not significantly influence the N2O emissions after fertilization. In contrast, the concentrated application of the final products led to contradictory results. Within the solid processing chain, utilization of pellets considerably increased the N2O emissions by factors of 2.7 (field, 2015), 3.5 (field, 2016), and 7.3 (incubation) compared to separated solid. Fertilization with N-rich ammonium sulfate solution led to the lowest emissions within the liquid processing chain. It can be concluded that the input of less recalcitrant organic C into the soil plays a greater role in N2O release after fertilization than the input of ammoniacal N. Digestate processing did not generally reduce emissions but apparently has the potential to mitigate N2O emissions substantially if managed properly.